Factors associated with poor sleep quality among dental students in Malaysia - Yong Jie, Khor; Mohamad, Noraini; Mohd Adnan, Munirah; Mohd Nor, Nor Azlida; Abdul Hamid, Nor Faharina; Abllah, Zurainie (PeerJ Inc., 2024)
Background Good sleep quality is crucial for dental students as they must have optimal cognitive function, memory, and decision-making to accomplish their learning requirements. This study aims to determine sleep quality, its associated factors, and the association between sleep quality and academic performance among dental students in Malaysia.